2017
DOI: 10.1371/journal.pone.0176571
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of urea-based soluble epoxide hydrolase inhibitors from the plants in the order Brassicales

Abstract: Recently, dibenzylurea-based potent soluble epoxide hydrolase (sEH) inhibitors were identified in Pentadiplandra brazzeana, a plant in the order Brassicales. In an effort to generalize the concept, we hypothesized that plants that produce benzyl glucosinolates and corresponding isothiocyanates also produce these dibenzylurea derivatives. Our overall aim here was to examine the occurrence of urea derivatives in Brassicales, hoping to find biologically active urea derivatives from plants. First, plants in the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 76 publications
2
11
0
1
Order By: Relevance
“…The search for therapeutics in nature that could alter epoxy-fatty acid levels has recently intensified. Plant-derived sEH inhibitors have recently been identified from Cimicifuga dahurica roots and from plants in the order Brassicales (Kitamura et al, 2017; Thao et al, 2017). These plant-derived sEH inhibitors have not been tested for favorable renal and cardiovascular actions.…”
Section: New Vistasmentioning
confidence: 99%
“…The search for therapeutics in nature that could alter epoxy-fatty acid levels has recently intensified. Plant-derived sEH inhibitors have recently been identified from Cimicifuga dahurica roots and from plants in the order Brassicales (Kitamura et al, 2017; Thao et al, 2017). These plant-derived sEH inhibitors have not been tested for favorable renal and cardiovascular actions.…”
Section: New Vistasmentioning
confidence: 99%
“…The addition of a meta -methoxy to the phenyl ring ( 8 – 14 ) generally decreased IC 50 values compared to unsubstituted analogues ( 1 – 7 ). This indicated that methoxy groups at meta positions can enhance sEH inhibition, as has been demonstrated with benzyl-containing urea-based natural sEH inhibitors . A second, para -methoxy ( 15 – 17 ), however, did not improve inhibitory potency.…”
Section: Resultsmentioning
confidence: 64%
“…This could be particularly important in developing countries. Previously, a number of chemicals from a variety of natural sources have been identified as sEHI, including urea- and amide-based inhibitors from plants in the order Brassicales. , However, a large number of these compounds have a low potency or their concentrations in the plant are insufficient for clinical application.…”
mentioning
confidence: 99%
“…Ações anti-inflamatórias foram citadas, Tenci et al (2017) apontaram as macamidas e metabólitos lipofílicos de extratos da maca, como possível tratamento contra a dor osteoarticular e neuropática. Para Kitamura et al (2017), o composto químico 1,3-Bis(3-metoxibenzil), demonstrou ação analgésica esperada contra a dor inflamatória induzida em ratos. Nos estudos de Almukadi et al, 2013, as macamidas atuaram no sistema nervoso central para fornecer efeitos analgésicos, antiinflamatórios ou neuroprotetores, modulando a liberação de neurotransmissores.…”
Section: Resultsunclassified